2016
DOI: 10.14309/crj.2016.136
|View full text |Cite
|
Sign up to set email alerts
|

Long QT Syndrome and Duodenal Ampullary Adenoma: A New Association

Abstract: KCNQ1 gene mutation has a well-known association with long QT syndrome (LQTS). However, recent studies suggest that it may be implicated in intestinal neoplasia. We present a 27-year-old Hispanic man with a known history of LQTS secondary to KCNQ1 mutation, who presented with painless jaundice. Endoscopic retrograde pancreatic cholangiography revealed a prominent ampulla, with histology consistent with ampullary adenoma with high-grade dysplasia. Further endoscopic studies did not suggest familial adenomatous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The KCNQ1 gene is highly expressed in peripheral blood leukocytes, the heart, prostate, inner ear blood vessels, stomach, small intestine, kidney, and pancreas, expressed in tissues that are critical for ion homeostasis (12,13). Humans carrying germline mutations in KCNQ1 develop a range of pathologies, most notably cardiac arrhythmia (long and short QT, Jervell and Lange-Nielsen syndrome), but also hearing loss, elevated gastrin levels, gastric hyperplasia, and in some cases gastric neoplasia (14)(15)(16)(17). These phenotypes have been modeled in KCNQ1 knockout mice which develop inner ear defects, imbalance, chronic gastritis, gastric hyperplasia, and gastric metaplasia (18).…”
Section: Introductionmentioning
confidence: 99%
“…The KCNQ1 gene is highly expressed in peripheral blood leukocytes, the heart, prostate, inner ear blood vessels, stomach, small intestine, kidney, and pancreas, expressed in tissues that are critical for ion homeostasis (12,13). Humans carrying germline mutations in KCNQ1 develop a range of pathologies, most notably cardiac arrhythmia (long and short QT, Jervell and Lange-Nielsen syndrome), but also hearing loss, elevated gastrin levels, gastric hyperplasia, and in some cases gastric neoplasia (14)(15)(16)(17). These phenotypes have been modeled in KCNQ1 knockout mice which develop inner ear defects, imbalance, chronic gastritis, gastric hyperplasia, and gastric metaplasia (18).…”
Section: Introductionmentioning
confidence: 99%
“…Ampullary adenomas, representing 5% of gastrointestinal neoplasms, are often asymptomatic and detected through upper endoscopy [ 4 ]. Symptoms of ampullary adenomas presenting with jaundice related to biliary obstruction caused by a tumor are rare [ 5 , 6 ]. Hornick et al reported that clinical jaundice was the strongest independent predictor of cancer among all ampullary tumors [ 2 ].…”
Section: Discussionmentioning
confidence: 99%